DEVELOPMENT OF SWAV MEDIA (SPARKOL WHITEBOARD ANIMATION VIDEOSCRIBE) IN THE DIRECT INSTRUCTION MODEL TO IMPROVE INTEREST AND LEARNING OUTCOMES - Lovry Arindo Setiawan (STKIP PGRI TULUNGAGUNG, 2025)
This study aims to describe the validity, practicality, and effectiveness of SWAV (Sparkol Whiteboard Animation Videoscribe) media in the direct instruction model in increasing the interest and learning outcomes of ninth-grade students at SMPN VI Tulungagung in congruence and similarity. The type of research used is RD development research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection methods used questionnaires and student learning outcome test instruments. The results of this study obtained an average score of 3.79 from media expert validators, which is considered valid. The average score from subject matter expert validators was 3.7, which is also considered valid. The practicality score from subject matter experts was 3.75, which is considered practical for use. Meanwhile, the small class trial validity score was 3.87 and the large class score was 3.81. The small class media practicality score was 3.87 and the large class score was 3.93. To determine the effectiveness of this media, it was proven by the average pre-test score of 55.74 and the post-test score of 82.70. Based on the t-test calculation using SPSS, a 2-tails significance value of 0.0000.005 was obtained, so H0 was rejected and H1 was accepted. The conclusion of this study is that the SWAV media is valid, practical, and effective for increasing the interest and learning outcomes of ninth-grade students.